PENGARUH PARKIR DI BADAN JALAN TERHADAP KINERJA RUAS JALAN TIMOR RAYA KM 8+800 SAMPAI DENGAN KM 9+000 - Lifu, Aldi Fernando; Seran, Engelbertha N. Bria; Mooy, Merzy; Usboko, Gregorius Paus (Program Studi Teknik Sipil Universitas Katolik Widya Mandira, 2023)
Development of socio-economic activities occurs linearly with respect to the road network. Along the edge of the Timor Raya Timor Raya road Km 8+800 to Km 9+000 the side barriers are now getting higher, both due to vehicle parking on the road body, as well as due to vehicles entering and leaving the parcel (access) and pedestrians on the shoulder of the road and road crossings. Traffic problems that arise due to the activity of vehicles parked on the road are of course detrimental to road users such as when the vehicle is parked or when the vehicle exits the parking lot, therefore parking controls on the Timor Raya road Km 8+800 to Km 9+000 is the most important thing to do to control traffic so that congestion, pollution, noise can be minimized. Based on the analysis conducted using the Indonesian Highway Capacity Manual (MKJI, 1997). It is known that the peak volume occurred on Monday, 08 May 2023 at 17.30-18.30 WITA with a volume of 2162.75 PCU/hour, a capacity of 2366.63 PCU/hour, and the performance of Jalan Timor Raya, Oesapa Km 8+800 to Km 9+ 000, is at service level E with a DS value of 0.91. with a light vehicle free flow speed of 35.8 km/hour and an average speed of 22 km/hour. in conditions without light vehicle (LV) and heavy vehicle (HV) parking on the road, enter service level D where the DS value reaches 0.78, with a capacity of 2781.83 pcu/hour, free flow speed of light vehicles 38.9 km/hour and an average speed of 28 km/hour. Whereas in conditions without parking at the entrance to the service level C where the DS value reaches 0.71, with a capacity of 3019.31 pcu/hour, the free flow speed of light vehicles is 42.6 km/hour and the average speed is 32 km /hour.